University proceedings. Volga region. Medical sciences - K.I. Sergatskiy; D.V. Ulybina; A.S. Kibitkin; A.S. Ivachev; I.V. Inkin (Известия высших учебных заведений. Поволжский регион: Медицинские науки)
This article examines the legal issues related to kidney transplantation, which are relevant not only in Russia, but also in the international arena, where the interests of human rights and medical necessity collide. Significant differences in the legislation of different countries have been identified, causing problems in combating phenomena such as transplant tourism and organ trafficking. The legal regulation of kidney transplantation requires not only consideration of medical and ethical standards, but also the development of effective enforcement mechanisms to prevent abuse and protect the rights of all participants in the process.